Molecular cytogenetics characterization of seven small supernumerary marker chromosomes derived from chromosome 19: Genotype-phenotype correlation and review of the literature - Recalcati, Maria Paola; Bonati, Maria Teresa; Beltrami, Nicola; Cardarelli, Laura; Catusi, Ilaria; Costa, Asia; Garzo, Maria; Mammi, Isabella; Mattina, Teresa; Nalesso, Elisa; Nardone, Anna Maria; Postorivo, Diana; et al. (European journal of medical genetics, 2018)
Only a few subjects carrying supernumerary marker chromosomes derived from 19 chromosome (sSMC(19)) have been described to date and for a small portion of them the genic content has been defined at the molecular level. We present seven new different sSMCs(19) identified in eight individuals, seven of whom unrelated. The presence of the sSMC is associated with a clinical phenotype in five subjects, while the other three carriers, two of whom related, are normal. All sSMCs(19) have been characterized by means of conventional and molecular cytogenetics. We compare the sSMCs(19) carriers with a clinical phenotype to already described patients with gains (sSMCs or microduplications) of overlapping genomic regions with the aim to deepen the pathogenicity of the encountered imbalances and to assess the role of the involved genes on the phenotype. The present work supports the correlation between the gain of some chromosome 19 critical regions and specific phenotypes.